Characteristics and mechanisms to control a COVID‐19 outbreak on a leukemia and stem cell transplantation unit. (12th December 2020) - Greiner, Jochen; Götz, Marlies; Malner‐Wagner, Waltraud; Wendt, Constanze; Enders, Martin; Durst, Christine; Michel, Detlef; von Harsdorf, S; Jung, Susanne
Abstract: Immunosuppressed patients like patients with leukemia or lymphoma, but also patients after autologous or allogeneic stem cell transplantation are at particular risk for an infection with COVID‐19. We describe a COVID‐19 outbreak on our leukemia and stem cell transplantation unit (LSCT‐Unit) originating from a patient with newly diagnosed acute myeloid leukemia. The patient was treated with intensive induction chemotherapy and we characterize the subsequent outbreak of COVID‐19 on a LSCT‐Unit. We describe the characteristics of the 36 contacts among the medical team, the results of their PCR and antibody tests and clinical aspects and features of infected employees. Of these 36 close contacts, 9 employees of the LSCT‐Unit were infected and were tested positive by PCR and/or antibody‐testing. 8/9 of them were symptomatic, 3/9 with severe, 5/9 with mild symptoms, and one person without symptoms. Due to stringent hygiene measures, the outbreak did not lead to infections of other patients despite ongoing clinical work. Moreover, we demonstrate that incubation period and clinical course of a COVID‐19 infection in an immunosuppressed patient could be unusual compared to that of immunocompetent patients. Consistent PCR and antibody testing are helpful to understand, control, and prevent outbreaks. For the safety of health‐care workers and patients alike, all employees wore FFP2 masks and were trained to adhere to several further safety guidelines. The implementation of rigorous hygiene measures is the key to controlling an outbreak and preventing infections of other patients. Abstract :